Cross Border Pollution - Private International Law Problems in Claiming Compensation - Szakats, Alexander (Victoria University of Wellington Law Review, 2001)
In this paper the late Professor Szakats offers a review of the private international law aspects of the damage caused by the discharge, of poisonous waste from a gold extraction enterprise in Romania, into a river which flowed into the river Tisza and through Hungary. It is fitting that this paper relates to Hungary and the much loved River Tisza – steeped in history and a source of inspiration to poet and patriot alike. I stood there, silent, without stirring, As if my feet were rooted to the spot, My soul intoxicated by a sweet, profound ecstasy Induced by nature's eternal beauty. Oh nature, oh glorious nature! What language would dare compete with you? How splendid you are! The more you are silent, The more you say, the more the beauty of your expression. Sándor Petófi, The Tisza